Competency framework for researchers in the public scientific and technological organizations in Vietnam - Giang, Tu Thao Huong; Huy, Tran Quang; Tuyet, Vu Thi Anh; Hong, Nguyen Thi (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2021)
Competency framework for human resource development has been studied widely with publications in scientific journals. However, there are only a few publication about competency framework for researcher development in Vietnam. This paper aims to proposal a competency framework for researchers based on literature review, international experiences and empirical analysis of survey data in Vietnamese Public Scientific and Technological Organizations. Data from 600 researchers has been analyzed by confirmatory factor analysis (CFA) and structure equation model (SEM) to validate the proposed competency framework for researcher performance improvement and to applied for training and development activity in research organizations. Code: 21053101